FACULTY MEMBERS WITH REGARD TO USE OF LIBRARY IN TIRUNELVELI DISTRICT : A CASE STUDY (International Journal of Food and Nutritional Sciences, 2022)
Library book circulation or library lending comprises the activities around thelending of library books and other material to users of a lending library. A circulation orlending department is one of the key departments of a library Periodicals can have some advantages over books depending on the information needed. However, when using periodicals, it is important to understand the difference between scholarly and popular documents. They include journals, newspapers and magazines. Serials are very unique, contain current information and very useful for study, teaching, learning and research purpose. The introduction of electronic resources is continuing impact on library collection. The term serial is used in a broader term to refer to the periodically published documents such as periodicals, journals, magazines, bulletins, newsletters and research institutions, newspapers.The use of online resources in libraries is aimed at broadening the range of available information resources within the library and adding value to the content by making themaccessible through digital means so that the researchers, and the entire members of the faculty community can access them anytime and anywhere. Electronic as an adjective relating to activities or processes mediated or enabled through the use of the computer, frequently by means of telecommunication links. Internet means a network of network which permits computers to communicate via a variety of languages called protocols. The internet may be used for electronic mail, discussion groups, file transfers, and webservices. Protocols include FTP -file transfer protocol, HTTP - for the transfer of webpages from a server to a browser, and SMTP for e-mail transfer.Further, the study explains that there is significant difference among the mean scores of faculty members and the satisfaction level of using the overall library facilities” as the ‘p’ value is not significance to calculated value. It is clearly seen from the above analysis that in all the categories of Professors,Associate Professors and Assistant Professors of the faculty members used the library in book circulation which is more. It is clearly seen from the above analysis that in all the categories of Professors,Associate Professors and Assistant Professors of the faculty members used periodicals inthe Library in more and the use of periodicals are less.The study concluded that majority of the Professors, Associate Professors andAssistant Professors of the faculty members used online resources. The study further reveals that all the categories of faculty members were more satisfied with the library and services and functions. The respondents in three categories have given first priority for the electronic reference services of ‘e-mail reference’. ‘Social media’ and ‘online chatreference are the second and third preferences given by the respondents. The least preference was given for the type of ‘Ask-A librarian service’. The study further reveals that the respondents in the three categories have given first priority for the problem of‘Not enough terminals to access information’. ‘Slow speed’ and ‘Not easy to search’ are the second and third preference given by the respondents. It is clearly seen from the above analysis that in all the categories of Professors,Associate Professors and Assistant Professors of the faculty members used the library in book circulation which is more. Hence, the study concluded that the null hypotheses “There is no significance difference among the gender of faculty members in using the library services.” is rejected and invalid as the ‘p’ value is not significance to calculated value. Hence, there is a significance difference among the gender of faculty members in using the Library services.